Efficient and simultaneous removal of aflatoxin B1, B2, G1, G2, and zearalenone from vegetable oil by use of a metal–organic framework absorbent. (30th August 2023) - Du, Qiuling; Zhang, Wei; Xu, Ning; Jiang, Xianhong; Cheng, Jie; Wang, Ruiguo; Wang, Peilong
Graphical abstract: Highlights: MOF-235 removed aflatoxins and zearalenone from vegetable oils simultaneously. MOF-235 was reusable, and the removal of aflatoxins and zearalenone was efficient. MOF-235 exhibited no significant damages to nutrient composition of the oil. Oils treated with MOF-235 was nontoxic. Abstract: Vegetable oils are usually cocontaminated with different mycotoxins, including aflatoxins and zearalenone, which cause significant food safety issues. Establishment of multitarget, high-efficiency, and low-cost adsorption methods are considered to be ideal solutions for mycotoxin removal in vegetable oils. In this study, we used metal–organic frameworks (MOFs) were used for the simultaneous removal of aflatoxins and zearalenone from vegetable oils. The results showed that MOF-235 simultaneously removed, within 30 min, more than 96.1% of aflatoxins and 83.3% of zearalenone from oils, and oils treated with MOF-235 exhibited di minimis cytotoxicity. Thus, synthesized MOF-235 exhibited sufficient efficacy to remove the targeted residues, as well as safety and reusability, which could be applied as a novel potential adsorbent in the removal of multiple mycotoxins from contaminated vegetable oils.